Trade policy in a "GVC World": Multinational corporations and trade liberalization. (December 2020) - Anderer, Christina; Dür, Andreas; Lechner, Lisa
Abstract: The globalization of production is changing the political economy of trade policymaking: Traditional supporters of free trade (exporters seeking market access in foreign countries) are joined by new actors (companies needing intermediates from abroad for their production processes) in their lobbying efforts for trade liberalization. Multinational corporations (MNCs) play a crucial role in this new alliance due to their strong involvement in international trade and endowment with resources that can be used to lobby policymakers. We derive an argument from these premises that leads to the expectation of variation in trade policy outcomes across industries depending on their degree of integration in a global network of multinational corporations. Disaggregated data on the level of tariffs and speed of tariff cuts in preferential trade agreements, international mergers and acquisitions at the firm level, and MNC imports of intermediates by sector allow us to test the argument. The findings support our theoretical expectations. The paper sheds light on the processes and outcomes of trade policymaking in a globalized economy by further developing an existing argument about GVCs and trade policy outcomes as well as expanding on it by adding data on international corporate connections.